[Jóka Gémesi 7]
silent-film on Russian subject (like in the 407, 408), the work of the firemen from the beginning to the modern systems, german film about the coal-industry, the orogin of the salt, salt-mines in Transsylvania, german cartoon Fritz & Fratz, The Public Library in New York, baseball, 1943 educational-film about a single-seater airoplane mixed with cartoon, on the wing nazi symbol